2001
DOI: 10.1126/science.1057437
|View full text |Cite
|
Sign up to set email alerts
|

A High-Resolution Radiation Hybrid Map of the Human Genome Draft Sequence

Abstract: We have constructed a physical map of the human genome by using a panel of 90 whole-genome radiation hybrids (the TNG panel) in conjunction with 40,322 sequence-tagged sites (STSs) derived from random genomic sequences as well as expressed sequences. Of 36,678 STSs on the TNG radiation hybrid map, only 3604 (9.8%) were absent from the unassembled draft sequence of the human genome. Of 20,030 STSs ordered on the TNG map as well as the assembled human genome draft sequence and the Celera assembled human genome s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(68 citation statements)
references
References 22 publications
4
64
0
Order By: Relevance
“…1) [13][14][15] . When X-rays are used to randomly cleave DNA, neighboring markers are rarely separated, allowing linkage to be evaluated.…”
mentioning
confidence: 99%
“…1) [13][14][15] . When X-rays are used to randomly cleave DNA, neighboring markers are rarely separated, allowing linkage to be evaluated.…”
mentioning
confidence: 99%
“…Both publicly available 22,39 and our own mapping data position TPST1 unambiguously within the SDS critical region (Figure 3), with no evidence of duplication locally or elsewhere in the genome. Broad tissue distribution of TPST1 mRNA (Northern blot analysis in Ouyang et al 5 ) is consistent with multi-organ defects observed in SDS.…”
Section: European Journal Of Human Geneticsmentioning
confidence: 99%
“…We have used the Genethon 10 , Marshfield 11 and deCODE 12 microsatellite-based maps, GeneMap99 13 and TNG 14 radiation hybrid maps, the Whitehead yeast artificial chromosome (YAC)-based map and the BAC physical map 4 to evaluate the completeness and order of assembled sequences for chromosomes 2 and 4. Only a small number (,1%) of sequence-tagged sites (STSs) were not identified in the existing sequence; these included STSs from repetitive sequences, sequence polymorphisms and regions within known sequence gaps.…”
Section: Comparison To Physical and Genetic Mapsmentioning
confidence: 99%